A Taguchi coupled desirability function analysis of wire cut EDM behaviour of titanium dioxide filled aluminium matrix composite. (2020) - Alagarsamy, S.V.; Ravichandran, M.; Kumar, S. Dinesh; Sakthivelu, S.; Meignanamoorthy, M.; Chanakyan, C.
Abstract: The current investigation was, to optimize the parameters for wire cut electric discharge machining (WCEDM) of Al7075 alloy based matrix composite. The Al7075 alloy incorporated with TiO2 (10 wt.%) particles was produced by stir casting process. Experiments were carried out by selecting the various WCEDM parameters like pulse current (amps), pulse on-time (µs) and pulse off-time (µs). A Taguchi coupled desirability function analysis was employed to determine the optimal parameters with an objective to maximize the material removal rate (MRR) and minimize the surface roughness (SR). The optimum level of WCEDM parameters were obtained by a largest value of composite desirability (dG ). The optimal level of parameters obtained are pulse current at 160 amps, pulse on-time at 120 µs and pulse off-time at 50 µs. Moreover, analysis of variance (ANOVA) was applied to indicate the significant effect of parameters to the output responses. The results observed that, pulse current and pulse on-time are the most impact factors to influence the combined output responses. The contour plot indicates that interaction of machining parameters on the desired output responses.